Early Childhood Development : Situation Analysis for Zambia - Hasan, Rifat; Moucheraud, Corrina; Bakilana, Anne; Nadeau, Sophie (World Bank, Washington, DC, 2016)
Teenage pregnancies have potential negative consequences on the next generation. Children born to adolescent mothers are particularly at risk in terms of health, nutrition, cognitive and socio-emotional development. Evidence shows that the early years – especially the first 1,000 days – are crucially important for lifetime health, learning, and productivity. Particularly for the most vulnerable children and families, early childhood development (ECD) is a high return investment. This policy brief presents evidence on the health, nutrition and overall development of children in Zambia with a focus on those born to adolescent mothers. Analysis of issues such as infant and child mortality, malnutrition, incidence of illness, healthcare seeking behaviors, protective practices, late entry for school, pre-school experience and development are discussed.